Local Wisdom Value in Implementing of Merdeka Belajar Kampus Merdeka in Era Digital - Rifari Baron; Suwarsito Suwarsito; Chodidjah Chodidjah; Vivian Lisma Lestari (STAI Hubbulwathan Duri, 2022)
The study's purpose was to obtain the concept of the value of local wisdom in the digital era with the existence of an independent learning policy on an independent campus. This study analyzed all research data related to the value of local wisdom and MBKM that has been carried out by previous researchers. This study was a literature review research through a qualitative approach. The research data was taken from research results that have been published in national and international journals in the period 2010-2022. The data analysis stage used in this study was a qualitative approach which includes: data reduction, data presentation, and conclusion. The results of this study resulted in the concept of applying local wisdom values that were compatible with the application of the MBKM policy and were also related to advances in digital technology with all the demands for quality human resources. Educators and educational institutions must work together to develop local wisdom values in MBKM policy-based learning. Educators can use the results of this research as theoretical input for developing learning facilities